Prognostic value of cta-derived left ventricular mass in neonates with congenital heart disease - Ellmann, Stephan; Nickel, Julie-Marie; Heiß, Rafael; El Amrani, Nouhayla; Wüst, Wolfgang; Rompel, Oliver; Rueffer, Andre; Cesnjevar, Robert; Dittrich, Sven; Uder, Michael; May, Matthias (Diagnostics, 2021)
For therapeutic decisions regarding uni-or biventricular surgical repair in congenital heart disease (CHD), left ventricular mass (LVM) is an important factor. The aim of this retrospective study was to determine the LVM of infants with CHD in thoracic computed tomography angiographies (CTAs) and to evaluate its usefulness as a prognostic parameter, with special attention paid to hypoplastic left heart (HLH) patients. Manual segmentation of the left ventricular endo-and epicardial volumes was performed in CTAs of 132 infants. LVMs were determined from these volumes and normalized to body surface area. LVMs of patients with different types of CHD were compared to each other using analyses of variances (ANOVA). An LVM cutoff for discrimination between uni-and biventricular repair was determined using receiver operating characteristics. Survival rates were calculated using Kaplan–Meier statistics. Patients with a clinical diagnosis of an HLH had significantly lower mean LVM (21.88 g/m2) compared to patients without applicable disease (50.22 g/m2; p < 0.0001) and compared to other CHDs, including persistent truncus arteriosus, left ventricular outflow tract obstruction, transposition of the great arteries, pulmonary artery stenosis or atresia, and double-outlet right ventricle (all, p < 0.05). The LVM cutoff for uni-vs. biventricular surgery was 33.9 g/m2 (sensitivity: 82.3%; specificity: 73.7%; PPV: 94.9%). In a subanalysis of HLH patients, a sensitivity of 50.0%, specificity of 100%, PPV of 100%, and NPV of 83.3% was determined. Patient survival was not significantly different between the surgical approaches or between patients with LVM above or below the cutoff. LVM can be measured in chest CTA of newborns with CHD and can be used as a prognostic factor.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Cardiac computed tomography; Computed tomography angiography; Congenital heart disease; Heart imaging; Heart surgery; Hypoplastic left heart